Standards of care for medical management of acromegaly in pituitary tumor centers of excellence (PTCOE) - Giustina, A; Uygur, MM; Frara, S; Barkan, A; Biermasz, NR; Chanson, P; Freda, P; Gadelha, M; Haberbosch, L; Kaiser, UB; Lamberts, S; Laws, E; et al. (Springer, 2024)
Purpose: A series of consensus guidelines on medical treatment of acromegaly have been produced in the last two decades. However, little information is available on their application in clinical practice. Furthermore, international standards of acromegaly care have not been published. The aim of our study was to report current standards of care for medical therapy of acromegaly, using results collected through an audit performed to validate criteria for definition of Pituitary Tumor Centers of Excellence (PTCOE). Methods: Details of medical treatment approaches to acromegaly were voluntarily provided by nine renowned international centers that participated in this audit. For the period 2018–2020, we assessed overall number of acromegaly patients under medical treatment, distribution of patients on different treatment modalities, overall biochemical control rate with medical therapy, and specific control rates for different medical treatment options. Results: Median number of total patients and median number of new patients with acromegaly managed annually in the endocrinology units of the centers were 206 and 16.3, respectively. Median percentage of acromegaly patients on medical treatment was 48.9%. Among the patients on medical treatment, first-generation somatostatin receptor ligand (SRL) monotherapy was used with a median rate of 48.7%, followed by combination therapies with a median rate of 29.3%. Cabergoline monotherapy was used in 6.9% of patients. Pegvisomant monotherapy was used in 7 centers and pasireotide monotherapy in 5 centers, with median rates of 7.9% and 6.3%, respectively. Conclusions: Current standards of care in PTCOEs include use of first-generation SRLs as the first medical option in about 50% of patients, as recommended by consensus guidelines. However, some patients are kept on this treatment despite inadequate control suggesting that cost-effectiveness, availability, patient preference, side effects, and therapeutic inertia may play a possible role also in PTCOE. Moreover, at odds with consensus guidelines, other monotherapies for acromegaly appear to have a marginal role as compared to combination therapies as extrapolated from PTCOE practice data. Presence of uncontrolled patients in each treatment category suggest that further optimization of medical therapy, as well as use of other therapeutic tools such as radiosurgery may be needed.